Strategi Pemasaran Produk Kimbab Woku Cakalang Fufu Khas Sulawesi Utara - Lagarense, Bet El; Nasir, Nadila (Jurnal Hospitaliti, 2024)
Marketing strategies are used to increase sales of products being marketed, the development of a popular culture also requires entrepreneurs to be able to carry out various innovations in the field of marketing not only in terms of food but also as a means of satisfying curiosity about popular culture experienced by consumers. The Kimbab culinary product with cakalang fufu woku dishes is a new product that is made as a characteristic of North Sulawesi and makes this Manadonese food sought after and liked by many people. In this way, a marketing strategy is needed to promote culinary products to the public so that they can enjoy Kimbab products, Korean specialties with local flavors typical of North Sulawesi. 2) find out how the marketing strategy for kimbab products uses North Sulawesi special spices, woku cakalang fufu, in increasing regional culinary tourism potential.